Temporal dynamics of stomatal behavior: modeling and implications for photosynthesis and water use - Vialet-Chabrand, Silvere R.M.; Matthews, Jack S.A.; McAusland, Lorna; Blatt, Michael R.; Griffiths, Howard; Lawson, Tracy (American Society of Plant Biologists, 2017)
Stomata control gaseous exchange between the leaf and bulk atmosphere limiting CO2 uptake for photosynthesis and water loss by transpiration, and therefore determine plant productivity and water use efficiency. In order to function efficiently, stomata must respond to internal and external signals to balance these two diffusional processes. However, stomatal responses are an order of magnitude slower than photosynthetic responses, which lead to a disconnection between gs and A. Here we discuss the influence of anatomical features on the rapidity of stomatal movement, and explore the temporal relationship between A and gs responses. We describe how these mechanisms have been included into recent modelling efforts, increasing the accuracy and predictive power under dynamic environmental conditions, such as those experienced in the field.